The Effect of Organic Matter (Centrosema pubescens) and Rock Phosphate Application on the Activity of Phosphatase and P Fraction of Latosol Soil in Darmaga, Bogor - S Djuniwati; H.B Pulunggono; Suwarno . (Jurnal Ilmu Tanah dan Lingkungan, 2007)
One of the problems of acid soils such as Latosol is very low in P-availabi/ity due to high P-j'vcation in those soils. Sincesoils is deficiency of P, adaptation of plants and microorganisms to overcome deficiency of P in soil is by producing phosphatase. Phosphatase. is an enzyme that able to catalize transformation of organic P to inorganic P, and produced by plant roots, residual of plants and microorganisms. Organic mailer as a source of P besides N and energy formicroorganisms, and then rock phosphate as an alternative P fertilizer were used in this research. The objective of theresearch was to study the effect of organic matter (Centrocema pubescent) and rock phosphate application on phosphataseactivity and P fraction of Latosol soil from Darmaga, Bogor. The experiment was designed by completely randomized designwith two factors and three replications. The first factor was application of organic matter with the rate of 0, 2.5, and 5 %, and the second factor was application of rock phosphate with the rate of 0, 20, and 40 ppm P. Soil equivalent to four hundred grams of oven dried soil, organic matter, and rock phosphate were mixed based on the treatments of the experiment, and were placed in plastic pots, and then were incubated for 8 weeks period After incubation period, the soil were air dried and analyzed for phosphatase activity, available P, and organic and inorganic P. The result showed that organic mailer increased activities of acid and alkaline phosphatase, organic and inorganic-P of soil. On the other hand, rocle phosphate increased inorganic P but decreased activities of acid phosphatase,. Application of organic matter or rock phosphate on activity of acid phosphatase was higher (2.3-2.6 times) than on alkaline phosphatase. There was no effect of combinationbetween organic matter and rock phosphate on the activity of phosphatase and organic/inorganic P. Combination betweenorganic matter and rock phosphate Significantly affected available P. In each rates of rock phosphate given, the increasing rate of organic matter increased available P in their interactions, on the contrary, in each rates of organic matter, the increasing rate of rock phosphate did not affect available P in their interactions. However it was tended to decrease in therate of 40 ppm P.